Prevalence of pain and use of prescription opioids among older adults: results from the Brazilian Longitudinal Study of Aging (ELSI-Brazil)Research in context - Pricila H. Mullachery; Maria Fernanda Lima-Costa; Antônio Ignácio de Loyola Filho (Elsevier, 2023)
Summary: Background: Pain has a significant impact on people's quality of life. The use of prescription opioids to treat pain is associated with an increased risk of opioid use disorders and overdose death. We measured the prevalence of recurrent pain, prescription opioid use, and associations between chronic conditions and prescription opioid use among Brazilian older adults. Methods: We used data from the first population-based longitudinal study of aging in Brazil (ELSI-Brazil), 2019-2020 (mean age = 63.3; 54.4% female). Outcomes were: (1) experience of recurrent pain and (2) use of opioid analgesics in the past three months among those who experience pain. Exposures included selected health conditions, history of falls, and hospitalizations. Findings: Prevalence of pain (n = 9234) was 36.9% (95% CI: 32.6-41.1). Pain was reported more frequently by female participants, low-income individuals, and those with a previous diagnosis of arthritis, chronic back pain, depressive symptoms, history of falls, and hospitalizations. Prevalence of opioid use among those reporting pain (n = 3350) was 30% (95% CI: 23.1-38.0). Prevalence of opioid use was higher among female and single individuals. In adjusted models, arthritis, chronic back pain, and presence of depressive symptoms were associated with prescription opioid use. Interpretation: Prescription opioid use was reported by a sizable portion of the older adults who suffer from pain in Brazil. In a context of growing consumption of prescription opioids, opioid misuse has the potential to increase in the future. Surveillance of prescription opioid use is critical to prevent their harmful consequences. Funding: ELSI-Brazil was funded by the Brazilian Ministry of Health.